AirVA - Indoor Air Quality Monitoring and Control with Occupants Alerting System - Ramos, A. (2025)
The objective of this work is to detail the development of an IoT system to monitor the indoor air quality index and record the entry and exit of occupants of the same space. Data is collected, processed, and sent to a data server through the MQTT communication protocol. This server is responsible for storing and displaying information on the ThingsBoard platform. To evaluate the solution, the air quality index and people count were monitored in some classrooms of Polytechnic Institute of Guarda. The results obtained show that the prototype meets all the requirements proposed for the system.